RNA sequencing reveals changes in the microRNAome of transdifferentiating hepatic stellate cells that are conserved between human and rat - Laura Sabater; Luigi Locatelli; Fiona Oakley; Timothy Hardy; Jeremy French; Stuart M. Robinson; Gourab Sen; D. A. Mann; Jelena Mann (Scientific Reports, 2020)
Abstract MicroRNAs are small (~ 22nt long) noncoding RNAs (ncRNAs) that regulate gene expression at the post-transcriptional level. Over 2000 microRNAs have been described in humans and many are implicated in human pathologies including tissue fibrosis. Hepatic stellate cells (HSC) are the major cellular contributors to excess extracellular matrix deposition in the diseased liver and as such are important in the progression of liver fibrosis. We employed next generation sequencing to map alterations in the expression of microRNAs occurring across a detailed time course of culture-induced transdifferentiation of primary human HSC, this a key event in fibrogenesis. Furthermore, we compared profiling of human HSC microRNAs with that of rat HSC so as to identify those molecules that are conserved with respect to modulation of expression. Our analysis reveals that a total of 229 human microRNAs display altered expression as a consequence of HSC transdifferentiation and of these 104 were modulated early during the initiation phase. Typically modulated microRNAs were targeting kinases, transcription factors, chromatin factors, cell cycle regulators and growth factors. 162 microRNAs changed in expression during transdifferentiation of rat HSC, however only 17 underwent changes that were conserved in human HSC. Our study therefore identifies widespread changes in the expression of HSC microRNAs in fibrogenesis, but suggests a need for caution when translating data obtained from rodent HSC to events occurring in human cells.